Pancasila Dalam Perspektif Agama Islam Dan Relevansinya Dalam Kehidupan Bangsa di Era Kontemporer - Miftahul Khoiri; Muchamad Fahrizal Ali (Jurnal Studi Multidisiplin Qomaruna, 2026)
Pancasila, as the foundational philosophy of the Indonesian state, contains values that align with the teachings of Islam. Each principle of Pancasila embodies moral and spiritual aspects that can be found in Islamic teachings, namely the Qur’an and the Sunnah. This article aims to examine the values of Pancasila from the perspective of Islam and their relevance in the contemporary era. The research method used is a qualitative approach with a literature study technique, by reviewing various sources, both classical and modern, related to the theme of Pancasila and Islam. The results of the analysis show that Pancasila and Islam share normative harmony in building a just and harmonious social order. In the contemporary era, the values of Pancasila remain relevant as moral and ethical guidelines in facing the challenges of globalization, spiritual crisis, and moral degradation. The conclusion of this study emphasizes that the integration of Islamic values in the practice of national life through Pancasila can strengthen national identity, reinforce unity, and maintain a balance between material and spiritual progress in Indonesian society. Thus, Pancasila is not something that contradicts Islam but rather serves as a means of harmonizing national and religious values.